The Totorales of Huanchaco: Support of a Millenary Cultural Tradition - Iberico Portocarrero, Pedro (Espergesia, 2023)
This research focuses on northern Peru, particularly the resort town of Huanchaco, and highlights the traditional use of totora reeds as a millennia-old cultural element of the Chimú civilization. It details the importance of this plant as an essential raw material for the construction of the "caballito de totora," whose cultural symbolism transcends national borders. Additionally, it analyzes the significance of this tradition for the development of handicrafts and tourism in the northern region. The study is supported by a legal framework that includes conventions, resolutions, and ordinances that regulate the management of this crucial natural resource, notably the Ramsar Convention, which focuses on the conservation of wetlands worldwide. From an ethnobotanical perspective, the medicinal and nutritional uses of the totora are systematized. The factors contributing to the vulnerability of these natural ecosystems are presented. Similarly, the process of constructing a "caballito de totora", its dimensions and necessary characteristics for navigation, are explained. Lastly, the study identifies the problems, both of anthropogenic and natural origin, that threaten the long-term survival of this plant, which has grown since immemorial times in the wetlands of northern Peru.Keywords: Caballito de totora; cultural heritage; urban resilience; cultural tradition; Huanchaco; Chimú culture.